Fe-doped NiCoP nanosheet array rich in phosphorus defects as well as preparation method and application of Fe-doped NiCoP nanosheet array
By using Fe-doped NiCoP nanosheet arrays as a water electrolysis catalyst, the problems of insufficient activity and stability of NiCoP materials in water electrolysis catalysis were solved, and a low-overpotential, high-efficiency water electrolysis reaction was achieved.
Patent Information
- Application Number
- CN202511114845.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-11
- Publication Date
- 2025-10-31
AI Technical Summary
Existing NiCoP materials lack sufficient electrochemical active sites, conductivity, and cycling stability in water electrolysis catalysis, resulting in slow water electrolysis reaction kinetics, requiring high potential drive, and increasing energy consumption.
Using zeolite imidazole ester framework (ZIF) materials as templates, Fe-doped NiCoP nanosheet arrays rich in phosphorus defects were prepared by Fe ion doping and the introduction of phosphorus defects, thereby improving the specific surface area and conductivity of the material.
It significantly improves the catalytic activity and cycle stability of water electrolysis, lowers the energy barrier of redox reactions of electrode materials, and only requires a low overpotential to catalyze water electrolysis, exhibiting good electrochemical performance and stability.
Smart Images

Figure CN120866870A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrolytic water catalytic materials, and specifically relates to a phosphorus-defect-rich Fe-doped NiCoP nanosheet array and its preparation method. Background Technology
[0002] The core challenge in producing "green hydrogen" through water electrolysis lies in the slow kinetics of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), which require high potentials and increase energy consumption. Currently, high-performance catalysts heavily rely on scarce and expensive precious metals such as Pt, Ir, and Ru, hindering large-scale applications. Developing highly active, stable, and low-cost non-precious metal or low-precious metal catalysts is a current research hotspot. Among them, transition metal phosphides (TMPs) have attracted widespread attention due to their unique physicochemical properties.
[0003] In TMPs (Thinning Electrolytic Metals), bimetallic phosphides such as NiCoP are among the most widely studied electrode materials. However, single NiCoP materials are limited by insufficient electrochemical active sites, conductivity, and cycling stability, making it difficult to meet the needs of practical applications. Recent studies have shown that, on the one hand, designing catalytic materials using metal-organic frameworks (MOFs) as templates can increase the specific surface area of electrode materials; on the other hand, the conductivity of electrode materials can be improved by doping with metal ions and introducing defects. This invention utilizes zeolite imidazolium ester frameworks (ZIFs) as templates to increase the number of active sites in the material; and utilizes Fe ion doping and the introduction of phosphorus defects to improve the conductivity of the material, thereby enhancing the catalytic activity and cycling stability of water electrolysis. Summary of the Invention
[0004] The purpose of this invention is to provide a phosphorus-defect-rich Fe-doped NiCoP nanosheet array and its preparation method. The Fe-doped NiCoP nanosheet array with phosphorus defects obtained by this method has the advantage of significantly improving electrochemical performance.
[0005] The technical solution of this invention is: a phosphorus-defect-rich Fe-doped NiCoP nanosheet array and its preparation method, characterized by the following steps:
[0006] (1) A certain amount of cobalt source and 2-methylimidazole were completely dissolved in an appropriate amount of solvent. Then the two solutions were mixed, and a piece of nickel foam was immersed in the reaction solution. After standing at room temperature for 4 hours, it was washed and dried to obtain a Co-ZIF-L nanosheet array.
[0007] (2) Dissolve a certain amount of potassium ferrocyanide in an appropriate amount of deionized water, then immerse the Co-ZIF-L nanosheet array obtained in step (1) into the solution, soak at room temperature for a certain time, wash and dry to obtain Fe-Co PBA;
[0008] (3) The Fe-Co PBA obtained in step (2) and a certain amount of phosphorus source were placed in two quartz boats respectively, placed in a tube furnace, heated and phosphated in N2 atmosphere, and naturally cooled to room temperature to obtain Fe-NiCoP nanosheet array.
[0009] (4) The Fe-NiCoP nanosheet array obtained in step (3) is placed in a tube furnace and heated for reduction under a 5% H2 / Ar atmosphere. After natural cooling to room temperature, a phosphorus-defect-rich Fe-doped NiCoP nanosheet array, abbreviated as V, is obtained. p -Fe-NiCoP.
[0010] In step (1), the type of cobalt salt is not limited, including one or more of cobalt chloride, cobalt sulfate, and cobalt nitrate.
[0011] In step (1), 2-methylimidazole and cobalt salt are completely dissolved in a solvent. The type of solvent is not limited, including organic solvents and deionized water. Organic solvents include, but are not limited to, one or more of methanol, ethanol, and DMF.
[0012] In step (1), 2-methylimidazole and cobalt salt are completely dissolved in the solvent. The preferred molar concentration of 2-methylimidazole is 0.015 to 0.060 mol / kg, and the preferred molar concentration of cobalt salt is 0.12 to 0.48 mol / kg.
[0013] In step (2), the Co-ZIF-L nanosheet array is immersed in potassium ferrocyanide solution at room temperature. The preferred molar concentration of the potassium ferrocyanide solution is 0.015 to 0.045 mol / kg. The preferred immersion time is 4 to 8 hours.
[0014] In step (3), the phosphorus source includes, but is not limited to, sodium hypophosphite, red phosphorus, black phosphorus or one or more, preferably sodium hypophosphite.
[0015] In step (3), Fe-Co PBA is placed in a tube furnace for heating and phosphating. The preferred phosphating temperature is 250-450°C, and the preferred phosphating time is 1-3.5 hours.
[0016] In step (4), Fe-NiCoP nanosheets are placed in a tube furnace for heating and reduction. The reduction temperature is preferably 200-350°C, and the reduction time is preferably 0.5-2.5 hours.
[0017] In summary, the Fe-doped NiCoP nanosheet array rich in phosphorus defects of the present invention has the following beneficial effects:
[0018] (1) Using nickel foam as a substrate, ZIF arrays were grown and assembled on it, and nickel-cobalt-phosphorus nanosheets were prepared by high-temperature annealing. The advantages of ZIF materials, such as porous morphology and multiple active sites, were retained, while the conductivity and cycle stability of the materials were improved.
[0019] (2) The introduction of iron ions and the reduction treatment under an argon-hydrogen atmosphere increased the number of phosphorus vacancies, improved conductivity, increased active sites, generated more internal electron transport channels, and lowered the Gibbs free energy of the surface reaction, thereby reducing the energy barrier required for the redox reaction of the electrode material. In a 1M KOH electrolyte solution, only 240mV and 164mV OER and HER overpotentials are required to generate 100mA / cm². 2 The current density. Meanwhile, at 100 mA / cm². 2 At a current density of 1000 rpm, the overpotential remained essentially unchanged after 250 hours of reaction, demonstrating good cycle stability.
[0020] (3) The preparation method of the present invention is simple and efficient, demonstrating the positive influence of defects on the construction of metal phosphide electrode materials, and can be easily extended to construct other defect-modified electrode materials. Attached Figure Description
[0021] Figure 1 This is a scanning electron microscope image of Co-ZIF-L obtained in step (1) of Embodiment 1 of the present invention;
[0022] Figure 2 This is a scanning electron microscope image of Fe-Co PBA obtained in step (2) of Example 1 of the present invention;
[0023] Figure 3 This is a scanning electron microscope image of Fe-NiCoP obtained in step (3) of Example 1 of the present invention;
[0024] Figure 4 The V obtained in step (4) of Embodiment 1 of this invention p Scanning electron microscope image of Fe-NiCoP;
[0025] Figure 5 The Fe-NiCoP obtained in step (3) and the V obtained in step (4) of Embodiment 1 of this invention are... p X-ray diffraction pattern of Fe-NiCoP;
[0026] Figure 6 This is the OER polarization curve of the electrode material prepared in Example 1 of this invention in 1M KOH electrolyte solution;
[0027] Figure 7 This is the HER polarization curve of the electrode material prepared in Example 1 of this invention in 1M KOH electrolyte solution;
[0028] Figure 8 The V prepared in step (4) of Example 1 of this invention p OER cycle stability diagram of -Fe-NiCoP measured in 1M KOH electrolyte solution;
[0029] Figure 9 The V prepared in step (4) of Example 1 of this invention p HER cycle stability of Fe-NiCoP measured in 1M KOH electrolyte solution. Detailed Implementation
[0030] The preferred embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples.
[0031] Example 1:
[0032] (1) Take 0.44g of cobalt nitrate hexahydrate and 0.98g of 2-methylimidazole and dissolve them completely in 30g of deionized water. Then mix the two solutions and immerse a piece of nickel foam into the reaction solution. Let it stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L nanosheet array.
[0033] Scanning electron microscope image of the prepared Co-ZIF-L is shown below. Figure 1 As shown, the nanosheet array is arranged in a regular triangular leaf shape and has a smooth surface;
[0034] (2) Dissolve 0.5g of potassium ferrocyanide in 50g of deionized water, then immerse the Co-ZIF-L nanosheet array obtained in step (1) into the solution, soak at room temperature for 6 hours, wash and dry to obtain Fe-Co PBA;
[0035] Scanning electron microscope image of the prepared Fe-Co PBA is shown below. Figure 2 As shown, the nanosheet array becomes a distinct hollow structure, but the shape of the triangular blades remains unchanged.
[0036] (3) The Fe-Co PBA and 1.0g sodium hypophosphite powder obtained in step (2) were placed in two quartz boats respectively, placed in a tube furnace, heated to 350°C in N2 atmosphere and held for 2 hours, and then naturally cooled to room temperature to obtain Fe-NiCoP nanosheet array.
[0037] Scanning electron microscope image of the prepared Fe-NiCoP is shown below. Figure 3 As shown, the surface of the triangular blade becomes rough, but the overall structure remains unchanged;
[0038] (4) The Fe-NiCoP nanosheet array obtained in step (3) is placed in a tube furnace and heated to 250°C in a 5% H2 / Ar atmosphere and held for 1 hour. It is then naturally cooled to room temperature to obtain a phosphorus-defect-rich Fe-doped NiCoP nanosheet array, abbreviated as V. p -Fe-NiCoP;
[0039] The obtained V p Scanning electron microscope image of Fe-NiCoP as shown below Figure 4 As shown, the morphology of the triangular blade array did not change significantly;
[0040] The obtained V p The X-ray diffraction pattern of Fe-NiCoP is as follows: Figure 5 As shown, the phase of the sample is NiCoP;
[0041] The V obtained by the above steps p -Fe-NiCoP was used as an electrode material for water electrolysis, and its OER polarization curve in 1M KOH electrolyte solution was tested, as shown in the figure. Figure 6 As shown; the polarization curve of HER in 1 MkOH electrolyte solution is as follows. Figure 7 As shown. At 100mA / cm 2 At the specified current density, the overpotentials for OER and HER were 240 mV and 164 mV, respectively. The fact that only a relatively low overpotential is required to catalyze the reaction indicates good electrochemical performance.
[0042] The V obtained by the above steps p Fe-NiCoP was used as an electrode material for water electrolysis, and its cyclic stability of OER in 1M KOH electrolyte solution was tested. Figure 8 As shown; the cyclic stability of HER in 1M KOH electrolyte solution was tested, as shown. Figure 9 As shown, the overpotential remained essentially unchanged after 250 hours of reaction, demonstrating good stability.
[0043] Example 2:
[0044] (1) Take 0.66g of cobalt nitrate hexahydrate and 0.98g of 2-methylimidazole and dissolve them completely in 30g of deionized water. Then mix the two solutions and immerse a piece of nickel foam into the reaction solution. Let it stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L nanosheet array.
[0045] (2) Dissolve 0.5g of potassium ferrocyanide in 50g of deionized water, then immerse the Co-ZIF-L nanosheet array obtained in step (1) into the solution, soak at room temperature for 12 hours, wash and dry to obtain Fe-Co PBA;
[0046] (3) The Fe-Co PBA and 1.0g sodium hypophosphite powder obtained in step (2) were placed in two quartz boats respectively, placed in a tube furnace, heated to 350°C in N2 atmosphere and held for 2 hours, and then naturally cooled to room temperature to obtain Fe-NiCoP nanosheet array.
[0047] (4) The Fe-NiCoP nanosheet array obtained in step (3) is placed in a tube furnace and heated to 250°C in a 5% H2 / Ar atmosphere and held for 1 hour. It is then naturally cooled to room temperature to obtain a phosphorus-defect-rich Fe-doped NiCoP nanosheet array, abbreviated as V. p -Fe-NiCoP;
[0048] According to the V obtained in step (4) p Scanning electron microscope image of Fe-NiCoP and Figure 4 Similarly, V p -Fe-NiCoP exhibits a rough, triangular blade structure;
[0049] The V obtained by the above steps p -Fe-NiCoP was used as an electrode material for water electrolysis, and its polarization curves for OER and HER were tested in 1M KOH electrolyte solution. At 100 mA / cm²... 2 At the current density, the overpotentials of OER and HER were measured to be 250mV and 160mV, respectively.
[0050] Example 3:
[0051] (1) Take 0.44g of cobalt nitrate hexahydrate and 0.98g of 2-methylimidazole and dissolve them completely in 30g of deionized water. Then mix the two solutions and immerse a piece of nickel foam into the reaction solution. Let it stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L nanosheet array.
[0052] (2) Dissolve 1.0g of potassium ferrocyanide in 50g of deionized water, then immerse the Co-ZIF-L nanosheet array obtained in step (1) into the solution, soak at room temperature for 12 hours, wash and dry to obtain Fe-Co PBA;
[0053] (3) The Fe-Co PBA and 1.0g sodium hypophosphite powder obtained in step (2) were placed in two quartz boats respectively, placed in a tube furnace, heated to 350°C in N2 atmosphere and held for 2 hours, and then naturally cooled to room temperature to obtain Fe-NiCoP nanosheet array.
[0054] (4) The Fe-NiCoP nanosheet array obtained in step (3) is placed in a tube furnace and heated to 250°C in a 5% H2 / Ar atmosphere and held for 1 hour. It is then naturally cooled to room temperature to obtain a phosphorus-defect-rich Fe-doped NiCoP nanosheet array, abbreviated as V. p -Fe-NiCoP;
[0055] According to the V obtained in step (4) p Scanning electron microscope image of Fe-NiCoP and Figure 4 Similarly, V p -Fe-NiCoP exhibits a rough, triangular blade structure;
[0056] The V obtained by the above steps p -Fe-NiCoP was used as an electrode material for water electrolysis, and its polarization curves for OER and HER were tested in 1M KOH electrolyte solution. At 100 mA / cm²... 2 At the current density, the overpotentials of OER and HER were measured to be 256mV and 168mV, respectively.
[0057] Example 4:
[0058] (1) Take 0.44g of cobalt nitrate hexahydrate and 0.98g of 2-methylimidazole and dissolve them completely in 30g of deionized water. Then mix the two solutions and immerse a piece of nickel foam into the reaction solution. Let it stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L nanosheet array.
[0059] (2) Dissolve 0.5g of potassium ferrocyanide in 50g of deionized water, then immerse the Co-ZIF-L nanosheet array obtained in step (1) into the solution, soak at room temperature for 6 hours, wash and dry to obtain Fe-Co PBA;
[0060] (3) The Fe-Co PBA and 1.5g sodium hypophosphite powder obtained in step (2) were placed in two quartz boats respectively, placed in a tube furnace, heated to 300℃ in N2 atmosphere and held for 4 hours, and then naturally cooled to room temperature to obtain Fe-NiCoP nanosheet array.
[0061] (4) The Fe-NiCoP nanosheet array obtained in step (3) is placed in a tube furnace and heated to 250°C in a 5% H2 / Ar atmosphere and held for 1 hour. It is then naturally cooled to room temperature to obtain a phosphorus-defect-rich Fe-doped NiCoP nanosheet array, abbreviated as V. p -Fe-NiCoP;
[0062] According to the V obtained in step (4) p Scanning electron microscope image of Fe-NiCoP and Figure 4 Similarly, Vp -Fe-NiCoP exhibits a rough-looking triangular blade structure, but the structure is slightly collapsed;
[0063] The V obtained by the above steps p Fe-NiCoP was used as an electrode material for water electrolysis, and its linear sweep voltammetry curves for OER and HER were tested in 1M KOH electrolyte solution. The results were obtained at 100 mA / cm². 2 At the current density, the overpotentials of OER and HER were measured to be 249 mV and 163 mV, respectively.
[0064] Example 5:
[0065] (1) Take 0.44g of cobalt nitrate hexahydrate and 0.98g of 2-methylimidazole and dissolve them completely in 30g of deionized water. Then mix the two solutions and immerse a piece of nickel foam into the reaction solution. Let it stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L nanosheet array.
[0066] (2) Dissolve 0.5g potassium ferrocyanide in 50g deionized water, then immerse the Co-ZIF-L nanosheet array obtained in step (1) into the solution, soak at room temperature for 6 hours, wash and dry to obtain Fe-Co PBA;
[0067] (3) The Fe-Co PBA and 1.0g sodium hypophosphite powder obtained in step (2) were placed in two quartz boats respectively, placed in a tube furnace, heated to 350°C in N2 atmosphere and held for 2 hours, and then naturally cooled to room temperature to obtain Fe-NiCoP nanosheet array.
[0068] (4) The Fe-NiCoP nanosheet array obtained in step (3) is placed in a tube furnace and heated to 300°C under a 5% H2 / Ar atmosphere for 2 hours. After natural cooling to room temperature, a phosphorus-defect-rich Fe-doped NiCoP nanosheet array, abbreviated as V, is obtained. p -Fe-NiCoP;
[0069] According to the V obtained in step (4) p Scanning electron microscope image of Fe-NiCoP and Figure 4 Similarly, V p -Fe-NiCoP exhibits a rough-looking triangular blade structure, but the structure is slightly collapsed;
[0070] The V obtained by the above steps p -Fe-NiCoP was used as an electrode material for water electrolysis, and its polarization curves for OER and HER were tested in 1M KOH electrolyte solution. At 100 mA / cm²... 2At the current density, the overpotentials of OER and HER were measured to be 253mV and 171mV, respectively.
[0071] The embodiments described above are detailed descriptions of the technical solutions of the present invention and should be understood as specific implementation measures of the present invention. They are not intended to summarize the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention shall fall within the scope of protection that the present invention should enjoy.
Claims
1. A phosphorus-defect-rich Fe-doped NiCoP nanosheet array, characterized in that, The preparation method includes the following steps: (1) Dissolve 0.44g of cobalt nitrate hexahydrate and 0.98g of 2-methylimidazole completely in 30g of deionized water, then mix the two solutions, immerse a piece of nickel foam in the reaction solution, let stand at room temperature for 4 hours, wash and dry to obtain Co-ZIF-L nanosheet array; (2) Dissolve 0.5g potassium ferrocyanide in 50g deionized water, then immerse the Co-ZIF-L nanosheet array obtained in step (1) into the solution, soak at room temperature for 6 hours, wash and dry to obtain Fe-Co PBA; (3) The Fe-Co PBA and 1.0g sodium hypophosphite powder obtained in step (2) were placed in two quartz boats respectively, placed in a tube furnace, heated to 350°C in N2 atmosphere and held for 2 hours, and then naturally cooled to room temperature to obtain Fe-NiCoP nanosheet array. (4) The Fe-NiCoP nanosheet array obtained in step (3) is placed in a tube furnace, heated to 250°C in a 5% H2 / Ar atmosphere and held for 1 hour, and then naturally cooled to room temperature to obtain a phosphorus-defect-rich Fe-doped NiCoP nanosheet array.
2. The use of the phosphorus-defect-rich Fe-doped NiCoP nanosheet array obtained by the preparation method according to claim 1 as a catalyst for water electrolysis.